Pengaruh Pendidikan Karakter terhadap Hasil Belajar PAI kelas V di SD N 34 VII Koto Sungai Sarik - Rossa Lina; Wedra Aprison; Arman Husni; Salmi Wati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the results of research on November 24, 2021 at SD N 34 VII Koto Sungai Sarik. The researcher observed that students' bad character greatly affected students' learning outcomes. The problems identified include absenteeism, lack of attention in lessons, noisy behavior in class, and lack of motivation to do assignments. This study aims to determine the effect of character education on the learning outcomes of fifth grade Islamic religious education at SD N 34 VII Koto Sungai Sarik. The type of research used is quantitative with a correlational approach. The population is all fifth grade students (120 people), with a sample of 30 people selected using random sampling technique. The results of the analysis showed a significant influence between student character and Islamic religious education learning outcomes. The coefficient of determination shows that 50.2681% of student learning outcomes are influenced by student character, while the rest is influenced by other factors. This finding confirms that student character has an important role in learning outcomes, especially in Islamic religious education subjects at SD N 34 VII Koto Sungai Sarik.